2009
DOI: 10.1111/j.1600-0714.2009.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA amplification and expression of FADD in oral squamous cell carcinoma

Abstract: In tongue SCCs, the expression of FADD was higher when compared with that of adjacent areas, which might be determined via genomic amplification in 11q13.3. Thus, SCC cells with the expression of FADD are possibly more likely to become metastatic and to worsen survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 19 publications
(22 reference statements)
1
33
0
Order By: Relevance
“…This concept was supported by the fact that FADD is deficient in certain types of cancer (11,12). However, multiple studies have revealed that FADD is overexpressed in many other forms of cancer (14)(15)(16)(17). Consistent with previous observations, the present study indicated that FADD is overexpressed in pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This concept was supported by the fact that FADD is deficient in certain types of cancer (11,12). However, multiple studies have revealed that FADD is overexpressed in many other forms of cancer (14)(15)(16)(17). Consistent with previous observations, the present study indicated that FADD is overexpressed in pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 81%
“…FADD is located on chromosome 11q13, a region that is frequently amplified in several types of cancer, including lung, head and neck squamous cell carcinoma, laryngeal and pharyngeal carcinomas, and breast and ovarian carcinomas (13). FADD mRNA and protein levels are known to be increased in these forms of cancer (14)(15)(16)(17)(18). However, the role of FADD in these diseases remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous reports, high expression of FADD was associated with factors indicating poor prognosis in squamous cell carcinoma of the head and neck [14,27] and oral squamous cell carcinoma [28]. However, contradictory clinical associations of FADD expression were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…FADD is an adaptor molecule interacting with many kinds of death receptors and induces apoptosis by caspase-8 [12,13]. FADD expression was associated with metastasis in squamous cell carcinoma of the head and neck [14] and poor prognosis in oral squamous cell carcinoma [15] and lung adenocarcinoma [16]. Because the amplification of FADD does not confined in a single gene, TMEM16A or PPFIA1 , which are in close proximity to FADD , may be amplified concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This elevation is likely due to increased DNA amplification. 7,8 Moreover, positive FADD expression is significantly associated with LNM of oral (e.g., tongue) squamous cell carcinoma and worse survival. 7,8 (Tu -met ), primary tumors from patients with LNM (Tu +met ) and the matching LNM.…”
Section: Introductionmentioning
confidence: 99%